Analisis Penanganan Teroris Kelompok Mujahidin Indonesia Timur (MIT) Pasca Konflik Di Kabupaten Poso - I Ketut Yakobus; Rinto Z.W. Abidjulu; Yuyun Alfasius Tobondo; Feliks Arfid Guampe (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2023)
The slow process of handling and enforcing the law against the East Indonesia Mujahadin Terrorism (MIT) group in Poso Regency has triggered violence and killings of civilians and security forces. The objectives of this study are: 1) To identify and analyze the model of handling terrorists of the MIT group that has been carried out by the Government. 3) To identify and analyze the causes of the slow handling of MIT group terrorists. 3) To find an effective and efficient model in the handling of the MIT terrorist group. The research approach used in this study is descriptive qualitative with the number of informants of 15 people, each of whom is a representative of the Government, religious leaders, community leaders, NGOs, and the community. Determination of informants is carried out by purposive sampling. Meanwhile, data collection is carried out by means of observation, in-depth interviews, and documentation. The results showed that the model of handling terrorists of the East Indinesian Mujahideen group after the conflict in Poso Regency prioritized a hard power military approach and was not participatory. The military's dominance in the handling of terrorism after the Poso conflict has created a very high sense of dependence on the security forces. In addition, the handling of terrorism by the East Indonesia Mujahideen group is also repressive, in the sense that the security forces will act in the event of acts of violence or killings committed by the East Indonesia Mujahideen Terrorist Group against civilians and against security forces who are temporarily performing their duties. The approach model that needs to be considered in handling terrorism of the East Indonesia Mujahideen group after the conflict in Poso Regency is the Hybrid model. The choice on the Hybrid model is because this model is soft power, preventive and participatory.